2019
DOI: 10.2196/12454
|View full text |Cite
|
Sign up to set email alerts
|

When Similarity Beats Expertise—Differential Effects of Patient and Expert Ratings on Physician Choice: Field and Experimental Study

Abstract: Background Increasing numbers of patients consult Web-based rating platforms before making health care decisions. These platforms often provide ratings from other patients, reflecting their subjective experience. However, patients often lack the knowledge to be able to judge the objective quality of health services. To account for this potential bias, many rating platforms complement patient ratings with more objective expert ratings, which can lead to conflicting signals as these different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that consumers perceived expert reviews as more trustworthy and useful for purchasing behaviors (Holbrook, 1999; Kranzbühler et al, 2019). However, some researches manifested that consumer reviews displayed majority’s opinions and could be viewed as more valid information (Lo & Yao, 2019; Sundar, 2008).…”
Section: Consumer Reviews and Expert Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that consumers perceived expert reviews as more trustworthy and useful for purchasing behaviors (Holbrook, 1999; Kranzbühler et al, 2019). However, some researches manifested that consumer reviews displayed majority’s opinions and could be viewed as more valid information (Lo & Yao, 2019; Sundar, 2008).…”
Section: Consumer Reviews and Expert Reviewsmentioning
confidence: 99%
“…This component may recognize the elaborate processing phase of attention and evaluation, resulting in different amplitudes for positive and negative stimuli (Bayer et al, 2012;Herbert et al, 2008). and useful for purchasing behaviors (Holbrook, 1999;Kranzbühler et al, 2019). However, some researches manifested that consumer reviews displayed majority's opinions and could be viewed as more valid information (Lo & Yao, 2019;Sundar, 2008).…”
Section: Event-related Potentials In This Studymentioning
confidence: 99%